Determining a potential of the parabolic equation from partial boundary measurements*This work was supported by NSFC (61671009). (2nd August 2021) - Fan, Jiaming; Duan, Zhiwen
Abstract: We concern the operator ∂ t − Δ + q with the Dirichlet boundary conditions on a bounded domain in R n, n ⩾ 3, and show that the knowledge of the Dirichlet-to-Neumann map measured on a very small subset of the boundary determines the potential uniquely.